(untitled) (International Journal of Medicine & Health Research (IJMHR) (ISSN 2395-3586), 2024)
The cases of twenty two fractures of the ankle joint that involved the tibial plafond were reviewed. The fractures were classified in to five types according to the severity of the injury. Open reduction and internal fixation was performed using one third tubular plate for fibula and recon plate for the tibia. Bone grafting was done to augment the fixation and maintain the reduction. For each fracture treated Objective and Subjective evaluation is done. The objective and subjective scores are compared. With this method we noticed that the Type III & IV fractures also had a good or excellent result